Analisis kinerja berbasis Balanced Scorecard pada koperasi simpan pinjam - Farida Ainun Nikmah; Retno Mustika Dewi (MBR (Management and Business Review), 2021)
This study aims to assess the performance of the Koperasi Pasar (Koppas) Wanita in Jatiprahu Village using the Balanced Scorecard method. This is a quantitative descriptive study, data collected through documentation, interviews and questionnaires from 158 samples. The results of the analysis obtained that three of the four research variable perspectives had bad results, the financial perspective, internal business, as well as growth and learning have decreased assessment results compared to the previous year. While the customer perspective variable has a good assessment result, increased compared to the previous year’s assessment. The overall performance Koperasi Pasar Wanita Kartini is satisfactory. The management and supervisor of the cooperative need to improve the existing performance system, so that in the future performance of the cooperative will be better.